Low Common-Mode Gain Instrumentation Amplifier Architecture Insensitive to Resistor Mismatches - Zainul Abidin; Koichi Tanno; Shota Mago; Hiroki Tamura (Institute of Advanced Engineering and Science, 2016)
In this paper, an instrumentation amplifier architecture for biological signal is proposed. First stage of conventional IA architecture was modified by using fully balanced differential difference amplifier and evaluated by using 1P 2M 0.6μm CMOS process. From HSPICE simulation result, lower common-mode voltage can be achieved by proposed IA architecture. Actual fabrication was done and six chips were evaluated. From the evaluation result, average common-mode gain of proposed IA architecture is 10.84 dB lower than that of conventional one without requiring well-matched resistors. Therefore, the proposed IA architecture is suitable for biological signal processing.